(untitled) (Iraqi Journal of Medical Sciences, 2004)
Human malignant lymphomas are heterogeneous groups of tumors that differ in regard to clinical behaviour and survival. Many histological classifications had categorize the degree of malignancy of the neoplasm by histological, cytochemical, immunological and genetic criteria, but additional indices can be useful for a better definition of the aggressiveness of lymphoid tumors. Trace elements particularly copper (Cu) and Zinc (Zn) which are essential metals which are required for growth and proliferation of healthy cells as well as for normal lymphocyte maturation and regulation of immune function therefore the estimation of the intracellular concentration of these metals may be used as a marker alongside other biological indices to define the aggressiveness of the malignant lymphomas. Aim: To determine the intracellular lymphocyte Cu and Zn and its relation with the grades of NHL and the histotypes of HD. Patients & Methods: Trace elements Cu, Zn and Cu/Zn ratio was estimated in 42 patients with malignant lymphoma. Of them 23 patients had non Hodgkin’s lymphoma (NHL) [age range 5-75 years] and 19 patients had Hodgkin’s disease (HD) [age range 6-70 years]. They were compared with 19 age matched healthy control subjects [age range 7-70 years]. All patients were newly diagnosed and did not receive any medication. Intracellular lymphocyte Cu and Zn were estimated using flame atomic absorption spectrophotometer, Perkin-Ewer 400 and the classification and grading of the lymphoma were based on the Rye classification and N.C.I. system for HD and NHL respectively. Results: intracellular Cu and Cu/Zn ratio were significantly high while intracellular Zn was insignificantly low when compared to control group. Moreover, only lymphocyte Cu had correlated with the grades and the histotypes of NHL and HD respectively. Conclusion: Therefore, we may propose that in malignant lymphoma Cu and Cu/Zn ratio rather than Zn may be used as a diagnostic markers and for following up the patients alongside other biological indices, and that only intracellular Cu reflect the disease severity in NHL and therefore can be used as a prognostic marker. Keyword: Malignant Lymphoma, Trace elements Cu, Zn and Cu/Zn ratio Iraqi J Med Sci, 2004; Vol. 3(1):8-13